Examining the Profits and Losses of Medan City Roadside Ditch Scraping by the Medan City Government on MSMEs - Pranata, Sungguh Ponten (Journal of Business Management and Economic Development, 2024)
The practice of digging roadside ditches by the Medan City Government is an important part of the flood mitigation strategy and improvement of the urban drainage system. However, this practice not only provides benefits for reducing flood risk, but also has a significant impact on Micro, Small and Medium Enterprises (MSMEs) around the area. This research aims to investigate the dynamics of profit and loss from the practice of trenching for MSMEs in Medan, focusing on identifying the challenges they face and opportunities to improve the sustainability of their businesses. Through a triangulation approach, including direct surveys, interviews with stakeholders, and secondary data analysis, this study reveals the complexity of the impact of trenching practices on MSMEs and the adaptation strategies adopted. The results show that MSMEs experience accessibility problems, material losses, and damage to business infrastructure due to this practice. However, MSMEs have also taken adaptation steps such as product diversification and increased connectivity. Support from sustainability-oriented public policies has also helped MSMEs increase their competitiveness and resilience. Despite this, challenges in implementing sustainable policies remain the main focus, with limited resources and lack of coordination between government agencies as the main obstacles. In conclusion, this research highlights the need for a holistic approach and close collaboration between stakeholders to create an environment that supports the growth and sustainability of MSMEs amidst changes in urban infrastructure.